Nail fold Capillaroscopic Findings in Iranian Patients with Systemic Lupus Erythematosus - Rajaei, Alireza; Dehghan, Pooneh; Ariannia, Saideh (Novelty in Biomedicine, 2016)
Background: Systemic Lupus Erythematosus is a progressive autoimmune disease with a wide range of morphological and functional changes in microscopic examination of small blood vessels. Identification of vascular diseases at early stage, plays an essential role in the prevention of its’ vascular complications. Nailfold capillaroscopy (NFC) is a non-invasive, easy, painless, and accurate method for evaluation of microcirculation and could be used for this purpose. The vast majority of studies on capillaroscopy in lupus patients have shown that changes are not specified to lupus –unlike Systemic Sclerosis- and are more likely to overlap with other diseases. Therefore, it was decided to check capillaroscopic changes and evaluate morphological changes and capillary structure in terms of quality and quantity in lupus patients. Materials and Methods: Nail fold capillaroscopic findings of 114 patients aged 19-75 years old were reviewed in this study. The results were categorized as: a) normal, b) non-specific morphological abnormalities, and c) Scleroderma-like pattern. Results were analyzed qualitatively and quantitatively using SPSS 21 software. "Chi square" test was used to analyze the relationships between variables (P<0.05 was considered significant). Results: Our results show that Lupus –independent of any other microvascular risk factor can significantly affect the morphology and structure of blood circulation and these changes are shown with detail by nail fold capillaroscopy. Conclusion: Most of the findings are in line with similar studies performed by other investigators in this field. However, no specific pattern was recognized and microbleeding was higher in our patients with scleroderma-like pattern of involvement.